Symmetrical and unsymmetrical triphenylamine based diketopyrrolopyrroles and their use as donors for solution processed bulk heterojunction organic solar cells. Issue 102 (19th October 2016) - Patil, Yuvraj; Misra, Rajneesh; Chen, F. C.; Keshtov, M. L.; Sharma, Ganesh D.
Abstract : Two small moleculesDPP3 (D–π–A) andDPP4 (D–π–A–π–D) with triphenylamine (TPA) donors and diketopyrrolopyrrole (DPP) acceptors linked with ethyne linkers were designed and synthesized by the Pd-catalyzed Sonogashira cross-coupling reaction. Abstract : Two small moleculesDPP3 (D–π–A) andDPP4 (D–π–A–π–D) with triphenylamine (TPA) donors and diketopyrrolopyrrole (DPP) acceptors linked with ethyne linkers were designed and synthesized by the Pd-catalyzed Sonogashira cross-coupling reaction. Their photonic, electronic, thermal and computational properties were investigated. The red shift in the electronic absorption spectra ofDPP4 as compared toDPP3 is related to extended conjugation and increased donor–acceptor interaction. We have usedDPP3 andDPP4 as electron donors along with PC71 BM as an electron acceptor for solution processed bulk heterojunction organic solar cells. The solar cells prepared fromDPP3 :PC71 BM andDPP4 :PC71 BM (1 : 2) processed from chloroform (CF) exhibit a power conversion efficiency (PCE) of 2.23% ( J sc = 6.74 mA cm −2, V oc = 0.92 V and FF = 0.36) and 3.05% ( J sc = 8.26 mA cm −2, V oc = 0.88 V and FF = 0.42), respectively. The higher PCE of the device withDPP4 compared toDPP3 was demonstrated as to the higher hole mobility and broader IPCE spectra. The devices based onDPP3 :PC71 BM andDPP4 :PC71 BM processed with solvent additive (1 v% DIO, 1, 8-diiodooctane) showed PCE values of 4.06% and 5.31%, respectively. The device optimization results from the improvement of the balanced charge transport and better nanoscale morphology induced by the solvent additive.